Abrupt, Asynchronous Changes in Action Representations by Anterior Cingulate Cortex Neurons during Trial and Error Learning. (2nd April 2020) - Emberly, Eldon; Seamans, Jeremy K
Abstract: The ability to act on knowledge about the value of stimuli or actions factors into simple foraging behaviors as well as complex forms of decision-making. In striatal regions, action representations are thought to acquire value through a gradual (reinforcement-learning based) process. It is unclear whether this is also true for anterior cingulate cortex (ACC) where neuronal representations tend to change abruptly. We recorded from ensembles of ACC neurons as rats deduced which of 3 levers was rewarded each day. The rat's lever preferences changed gradually throughout the sessions as they eventually came to focus on the rewarded lever. Most individual neurons changed their responses to both rewarded and nonrewarded lever presses abruptly (<2 trials). These transitions occurred asynchronously across the population but peaked near the point where the rats began to focus on the rewarded lever. Because the individual transitions were asynchronous, the overall change at the population level appeared gradual. Abrupt transitions in action representations of ACC neurons may be part of a mechanism that alters choice strategies as new information is acquired.